Tandem autologous stem cell transplantation improves outcomes in newly diagnosed multiple myeloma with extramedullary disease and high-risk cytogenetics: a study from the chronic malignancies working party of the European society for blood and marrow transplantation - Gagelmann, Nico; Schönland, Stefan (Biology of blood and marrow transplantation, 2019)
Although high-dose therapy and autologous stem cell transplant combined with novel agents continues to be the hallmark of first-line treatment in newly diagnosed transplant-eligible multiple myeloma patients, the impact of tandem autologous or autologous/reduced-intensity allogeneic transplant for patients with extramedullary disease (EMD) and high-risk cytogenetics is not yet defined. Here, we analyzed clinical and cytogenetic data from 488 adult myeloma patients with EMD undergoing single autologous (n=373), tandem autologous (n=84), or autologous-allogeneic transplant (n=31) between 2003 and 2015. At least 1 high-risk abnormality was present in 41% (n=202), with del(17p) (40%) and t(4;14) (45%) the most frequent. More than 1 high-risk abnormality was found in 54%. High-risk cytogenetics showed worse 4-year overall survival (OS) and progression-free survival (PFS) of 54% and 29%, respectively, versus 78% and 49% for standard-risk cytogenetics (P < .001). Co-segregation of high-risk abnormalities did not seem to affect outcome. Regarding transplant regimen, OS and PFS were 70% and 43% for single autologous versus 83% and 52% for tandem autologous and 88% and 58% for autologous-allogeneic (P=.06 and P=.30). In multivariate analysis high-risk cytogenetics were associated with worse survival (hazard ratio [HR], 2.00; P=.003), whereas tandem autologous significantly improved outcome versus single autologous transplant (HRs, .46 and .64; P=.02 and P=.03). Autologous-allogeneic transplant did not significantly differ in outcome but appeared to improve survival, but results were limited because of small population (HR, .31). In conclusion, high-risk cytogenetics is frequently observed in newly diagnosed myeloma with EMD and significantly worsens outcome after single autologous, whereas a tandem autologous transplant strategy may overcome onset poor prognosis.